A secure authentication with key agreement scheme using ECC for satellite communication systems. (5th September 2018) - Qi, Mingping; Chen, Jianhua; Chen, Yitao
Summary: Recently, Liu et al came up with an authentication with key agreement scheme for securing communication over the low‐earth‐orbit satellite communication systems. However, this paper demonstrates that this scheme cannot provide perfect forward secrecy or defend against the smart card stolen attack, and has some very bad design defects, making it unpractical. Thus, to design a truly secure authentication scheme for satellite communication systems, this paper presents a new scheme, making use of the advantages of elliptic curve cryptography and symmetric cryptography. The security analyses by the widely used BAN logic and heuristic discussions demonstrate that our new scheme possesses perfect security properties and can defend against various well‐known malicious attacks. Moreover, our new scheme allows users to update passwords locally in accordance with their wishes, achieving a good user experience. Abstract : This paper demonstrates that Liu et al's scheme cannot provide perfect forward secrecy or defend against the smart card stolen attack, and has some very bad design defects, and then presents a new scheme. The security analyses by the widely used BAN logic and heuristic discussions demonstrate that our new scheme possesses perfect security properties and can defend against various well‐known malicious attacks. Moreover, our new scheme allows users to update passwords locally in accordance with their wishes, achieving a good user experience.